Interventions and Outcomes in Patients with Infectious Pseudomonas scleritis: A 10-Year Perspective. (3rd April 2019) - Ahmad, Sumayya; Lopez, Michelle; Attala, Marwan; Galor, Anat; Stanciu, Natalie A.; Miller, Darlene; Suh, Leejee; Albini, Thomas; Perez, Victor L.; Karp, Carol L.; Davis, Janet L.; Alfonso, Eduardo; et al.
ABSTRACT: Purpose : To identify interventional factors associated with improved visual results and faster time to resolution for patients with Pseudomonas scleritis. Methods : Retrospective study analyzing inciting factors, therapeutic modalities, and outcomes of patients with Pseudomonas scleritis. Results : A total of 24 patients were analyzed; 22 were treated as outpatients. All had resolution of infection and 58% ( n  = 14) maintained ≥20/200 vision. Medical therapy included topical and oral antibiotics; seven received additional subconjunctival injections; two were admitted for IV antibiotics. Patients presenting with ≥20/200 vision were more likely to maintain this level of vision ( n  = 8, 80%) compared to those presenting with severe vision loss ( n  = 5, 36%) ( p  = 0.04). A similar proportion of patients who received ( n  = 8, 61%) and did not receive ( n  = 5, 39%) oral steroids achieved 20/200 vision or better once infection resolved, p  = 1.0. Conclusions: Pseudomonas scleritis can be successfully managed in the outpatient setting. Oral steroids do not appear harmful in the treatment of this disease.